Clear Cell Papillary Renal Cell Carcinoma: A Potential Mimic of Conventional Clear Cell Renal Carcinoma on Core Biopsy - Heath Liddell; Anton Mare; Sean Heywood; Genevieve Bennett; Hin Fan Chan (Case Reports in Urology)
Clear cell papillary renal cell carcinoma (CCP-RCC) is a recently described, relatively uncommon variant of renal cell carcinoma (RCC) with a reported incidence of 4.1%. Thought to only arise in those with end stage renal disease, CCP-RCC is increasingly identified in those without renal impairment. CCP-RCCs have unique morphologic, genetic, and immunohistochemical features distinguishing them from both conventional clear cell renal cell carcinomas and papillary renal cell carcinomas. Immunohistochemically, these tumors are positive for CK7 and negative for CD10 and racemase. This is in contrast to conventional cell renal cell carcinomas (CK7 negative, CD10 positive) and papillary cell carcinomas (CK7, CD10, and racemase positive). These tumours appear to be indolent in nature, with no current documented cases of metastatic spread. We present the case of a 42-year-old female who presented with an incidental finding of a renal mass that on a core biopsy was reported as clear cell carcinoma, Fuhrman grade 1. She subsequently underwent a radical nephrectomy and further histological examination revealed the tumor to be a clear cell papillary renal cell carcinoma, Fuhrman grade 1.